The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1111/j.1395-3907.2003.00163.x
|View full text |Cite
|
Sign up to set email alerts
|

Topical versus peribulbar anaesthesia for cataract surgery

Abstract: ABSTRACT.Background: To assess and compare the efficacy and safety of topical versus peribulbar anaesthesia in patients undergoing routine cataract surgery. Methods: The unicentre, prospective, randomized, clinical interventional trial included 140 consecutive patients undergoing routine cataract surgery performed by one of two surgeons. The patients were randomly distributed to either peribulbar anaesthesia or topical anaesthesia. To assess intraoperative pain, each patient was asked immediately after surgery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 28 publications
3
24
0
1
Order By: Relevance
“…[8][9][10] Topical anaesthesia confers the advantages of relatively faster visual recovery and higher patient satisfaction, easy application, minimal discomfort on administration, rapid onset of anaesthesia, and lower cost. 5,[11][12][13] However, the use of a topical anaesthetic permits the patient's full ocular movement during surgery, requires patient compliance, and may involve the administration of supplemental anaesthesia. 5,12 Unpreserved lidocaine is the most frequently used and safest agent in topical anaesthesia.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[8][9][10] Topical anaesthesia confers the advantages of relatively faster visual recovery and higher patient satisfaction, easy application, minimal discomfort on administration, rapid onset of anaesthesia, and lower cost. 5,[11][12][13] However, the use of a topical anaesthetic permits the patient's full ocular movement during surgery, requires patient compliance, and may involve the administration of supplemental anaesthesia. 5,12 Unpreserved lidocaine is the most frequently used and safest agent in topical anaesthesia.…”
Section: Introductionmentioning
confidence: 99%
“…5,[11][12][13] However, the use of a topical anaesthetic permits the patient's full ocular movement during surgery, requires patient compliance, and may involve the administration of supplemental anaesthesia. 5,12 Unpreserved lidocaine is the most frequently used and safest agent in topical anaesthesia. Because of the shortacting effect, intraoperative and/or postoperative pain, and dissatisfaction may be associated with the use of topical lidocaine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They also concluded that as topical anesthesia is less invasive than peribulbar anesthesia, patients may require less intraoperative and postoperative monitoring with topical anesthesia than with peribulbar anesthesia. 21 There was no difference in visual acuity in the two groups after six weeks. They reported that visual rehabilitation in the postoperative period is faster with topical anesthesia, as it allows patients to see just after surgery, whereas the optic nerve and extraocular muscles may still be partially blocked by local anesthetics in patients who have undergone cataract surgery with peribulbar anesthesia.…”
Section: Discussionmentioning
confidence: 94%
“…Nevertheless, it is important that all conditions be evaluated prior to operation in older individuals with risk factors. Topical anaesthesia is very useful for outpatients and leads to fewer post-surgical complications (21), and previous studies have described the efficacy of topical anaesthesia in outpatient operations, even when performed by residents (22)(23)(24). Koolwijk et al (25) reported that outpatient cataract surgery is easy and safe with topical anaesthesia, with minimal complications.…”
Section: Discussionmentioning
confidence: 99%